Religiusitas Memediasi Pengaruh Love of Money Terhadap Persepsi Etika Tax Evasion - Langgeng Prayitno Utomo; Setia Budi Kurniawan; Etty Harya Ningsi; Retna Safriliana; Prihat Assih (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Lack of ethical awareness and ambitious attitudes of individuals in companies to enrich themselves through tax evasion are the main causes of the high number of tax evasion cases in 2024 which increased reports from law enforcement with 1,469 taxpayers being examined. With religiosity acting as a mediating variable, the purpose of this study was to determine how love of money affects the perception of Tax Evasion ethics. All accounting students who took part in tax briefing in Jombang Regency became the research population. The sample selection technique used was purposive sampling and obtained 168 samples. The SEM-PLS method was used in data analysis. Based on the results of the study, love of money significantly increases a person's perception of Tax Evasion ethics, while religiosity has a negative impact that can be ignored. In addition, love of money effectively mediates the influence between love of money and perception of Tax Evasion ethics.